2008
DOI: 10.1021/jf8002174
|View full text |Cite
|
Sign up to set email alerts
|

Walnut Polyphenols Prevent Liver Damage Induced by Carbon Tetrachloride and d-Galactosamine: Hepatoprotective Hydrolyzable Tannins in the Kernel Pellicles of Walnut

Abstract: The polyphenol-rich fraction (WP, 45% polyphenol) prepared from the kernel pellicles of walnuts was assessed for its hepatoprotective effect in mice. A single oral administration of WP (200 mg/kg) significantly suppressed serum glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) elevation in liver injury induced by carbon tetrachloride (CCl 4), while it did not suppress d-galactosamine (GalN)-induced liver injury. In order to identify the active principles in WP, we examined individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 29 publications
4
51
0
1
Order By: Relevance
“…Modulation of these antioxidant defenses clearly contributed to the strong antioxidant and hepatoprotective effect of MSE. The remarkable antioxidant effect of MSE may be related to the presence of ellagitannins and other phenoilc compounds, which can be synergistic in their action against lipid peroxidation (Haslam, 1996;Shimoda et al, 2008). Experimental evidence proved that whole plant extracts usually possess much better pharmacological activities than single isolated ingredients due to synergistic interactions between the individual components (Wagner & Ulrich-Merzenich, 2009;Williamson, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Modulation of these antioxidant defenses clearly contributed to the strong antioxidant and hepatoprotective effect of MSE. The remarkable antioxidant effect of MSE may be related to the presence of ellagitannins and other phenoilc compounds, which can be synergistic in their action against lipid peroxidation (Haslam, 1996;Shimoda et al, 2008). Experimental evidence proved that whole plant extracts usually possess much better pharmacological activities than single isolated ingredients due to synergistic interactions between the individual components (Wagner & Ulrich-Merzenich, 2009;Williamson, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They have attracted considerable attention due to their potent antioxidant effects (Haslam, 1996;Okuda, 2005). Previous studies revealed that the ellagitannin-rich fraction of walnuts exhibited hepatoprotective activity against CCl 4 -induced liver injury in mice and suppressed the elevated AST and ALT levels (Shimoda et al, 2008). Tellimagrandin I and II were shown to be the principal constituents responsible for the hepatoprotective effect of walnuts (Shimoda et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported apoptotic effect on HL-60 cells, antiinflammatory activity of casuarinin (9) (Yang et al 2000;Pan et al 2000), anti-dementia activity of tellimagradin II (6) and pentagallolylglucose (3) extracted from Sanguisorbae Radix (Lee et al 2005), anti-diabetic activity of pentagallolylglucose (3) extracted from Paeonia lactiflora roots (Baumgartner et al 2010), anti-oxidation activity of casuarinin (9) extracted from Terminalia arjuna (Chen et al 2004) and T. chebula (Cheng et al 2003), anti-oxidation and antitumor activities of pentagallolylglucose (3) (Okuda et al 2009), antibacterial activity of tellimagradin II (6) extracted from Rosa rugosa (Kamijo et al 2008), antioxidant activity and DPPH radical-scavenging activity of pedunculagin (5), casuarictin (4) and casuarinin (9) isolated from walnuts (Juglans regia L.), and preventive effect on liver damage induced by carbon tetrachloride of tellimagrandin II (6) and casuarictin (4) isolated from walnuts (J. regia L.) (Fukuda et al 2003;Shimoda et al 2008). Inhibitory effects of apple condensed tannins on compound 48/80-induced mast cell degranulation (Tokura et al 2005) and on histamine release from RBL cells (Kanda et al 1998) were reported.…”
Section: Introductionmentioning
confidence: 99%